Soluble Fiber Content And Acceptance In The Combination Of Avocado And Apple Juice - Luthfia Atikasari; Mohammad Jaelani; Yuwono Setiadi; Yuniarti Yuniarti; Ria Ambarwati (Journal of Nutrition Science, 2021)
Avocados and apples are one of the foods high in soluble fiber that can be processed into functional drinks as an alternative food in overcoming hypercholesterolemia. Knowing the soluble fiber content and acceptability in the combination of avocado and apple juice. This study used an experimental method with a randomized design, consisting of 3 formulas, namely 50:50, 60:40, and 70:30 with 4 treatments. Water soluble fiber content by using enzymatic test. Acceptance test on 30 women of childbearing age. Data analysis used one way ANOVA test. The average soluble fiber content in the juice combination formula were 50:50 (8,19 g), 60:40 (9,81 g) and 70:30 (11,01 g). The acceptability test for the 50:50 and 60:40 formulas was rated somewhat like to like with an average rating on each parameter, which was 2,77 to 3,73. The combination of avocado and apple juice contributes 25,61 – 37,98% of fiber to the WUS RDA. The most preferred formula in the acceptability test assessment was 50:50 with an average fiber content of 8,19 g which was able to meet 28,26 – 27,32% of the daily fiber requirement.